Developing an HMIS Architecture Framework to Support a National Health Care eHealth Strategy Reform : A Case Study from Morocco - Le Pape, Marc A. (Taylor and Francis, 2017)
An increasing number of low- and middle-income countries are receiving significant investments to implement health reform strategies featuring a health management information system (HMIS) as a fundamental eHealth intervention. We present the case of Morocco's first step toward the implementation of a national HMIS: the “urbanization” of its health information systems—an information architecture methodology designed to leverage existing capacity while ensuring sustainability of the new HMIS. We report on this process and share lessons learned, applicable to similar countries involved in HMIS interventions, including involving all stakeholders from inception to rollout, encouraging local ownership of the new HMIS, fostering active data usage among users, and leveraging existing personnel rotation policies when developing adoption strategies and facilitating capacity building efforts.